Model Of Full Day School Financial Management Under Environmental Dynamics - Purwanto, Purwanto (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
This study examines the portrait of operational management, unit cost of service and its influence on full day school revenue amidst environmental dynamics. The study was conducted through a case study approach. The research data are in the form of financial reports and profiles of school institutions. The analysis was carried out in three stages. First, operational ratio analysis to determine the development of the performance of operating income and operating costs of the institution during the observation year (2005-2022). Second, regression analysis to describe the function of cost per unit of service against the institution's income. Third, simulation analysis aims to determine the extent to which a product or service can be easily reconfigured to respond to environmental changes. The simulation analysis is seen from the aspects of: changes in service scale, addition of new service units, elimination of service units and transfer of service units. This study found the following results. First, the highest institutional income comes from student fees (28%), followed by full-day meal consumption (17%) and government subsidies for operations (18%). The highest institutional expenditure comes from salaries (29%), followed by full-day meal consumption (17%) and government subsidies for operations (18%). Second, the full-day meal service unit has the greatest influence on full-day school revenue followed by the elementary school and kindergarten service units. Thirdly, the modular system has the potential for school financial management under environmental dynamics.